The Effectiveness of Using The Method Of Educational Complexes in Developing Cognitive Motivation and Learning Some Basic Skills in Handball - Saleh Ali Danhash (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study investigated the impact of the educational complexes method on developing cognitive motivation among students, specifically aiming to show improvements in the experimental group's post-test results. An experimental methodology was employed, chosen for its effectiveness in controlling independent variables and accurately measuring their influence on dependent variables. The research sample comprised 86 second-year students from the Faculty of Physical Education and Sports Sciences at Al-Maaref University for the 2024-2025 academic year, selected via purposive sampling. The study focused on two crucial handball skills: dribbling and shooting. Data were collected using a cognitive motivation scale questionnaire, a skill test around a rectangular field, and a shooting accuracy test. Following pre-tests and the main experimental intervention, post-tests for skill and cognitive motivation were administered. Analysis of the data (Tables 1, 2, and 3) revealed a noticeable improvement in learning levels for both cognitive motivation and handball skills across both the experimental and control groups when comparing pre-test to post-test results. The findings conclude that the educational complexes method effectively increases students' cognitive motivation and significantly enhances the learning process for handball dribbling and shooting skills.